Islam Di Percut Sei Tuan: Studi Masyarakat Batak Muslim Abad Ke-20 - Nazirah Al Zany; Siti Azzuhra; Sri Rizki Wardani Simanjuntak; Amri Amri (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
In writing this article with the title Islam in Percut Sei Tuan: a study of the Batak Muslim community in the 20th Century. With the urgency of Malayunization, the Batak community carried out it in order to get a place to live and work with salaries paid by the Dutch. The research we conducted focused on one village, namely Percut village. Percut Village is one of the villages in Percut Sei Tuan sub-district. When Indonesia was not yet independent, Percut village existed under the Percut vocational school. The Percut Vocational School is led by a vocational sultan named Sultan Matseh who is a descendant of the Deli kingdom. Melunization carried out by the Batak people who lived in the Melayu land of Deli was like eliminating clans and becoming Muslims at that time.